2018
DOI: 10.1108/jhr-11-2017-010
|View full text |Cite
|
Sign up to set email alerts
|

Parental feeding practice is associated with child’s body mass index in Thai school-aged children

Abstract: Purpose Parental feeding practice (PFP) plays an important role in child’s eating behavior and weight status, but less information is available about its role in the Thai family setting. The purpose of this paper is to examine the influence of PFP on child’s gender and body mass index (BMI). Design/methodology/approach Participants included 227 parents-child dyads from the suburban area of Nakhon Pathom province, Thailand. Children aged 9-12 years and parents who were either child’s mother, father or grandfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…A significant relationship between the genders of children with parental feeding strategies was not observed. However, evidence shows that parents used more food restriction and monitoring for their girls than boys in ages 9–12 years (Yamborisut, Visetchart, Thasanasuwan, & Srichan, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant relationship between the genders of children with parental feeding strategies was not observed. However, evidence shows that parents used more food restriction and monitoring for their girls than boys in ages 9–12 years (Yamborisut, Visetchart, Thasanasuwan, & Srichan, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…shows that parents used more food restriction and monitoring for their girls than boys in ages 9-12 years (Yamborisut, Visetchart, Thasanasuwan, & Srichan, 2018). Children who were eligible for school lunch program experienced significantly more restriction for weight control and pressure to intake enough food from their parents (p < .05).…”
Section: Effect Of Demographic Variables On Parental Feeding Practicesmentioning
confidence: 99%
“…Previous studies also reported that restrictions of food for weight was associated with higher BAZ. On the other hand, use of pressure was associated with lower BAZ (Wan et al, 2012;Entin et al, 2014;Do et al, 2015;Quah et al, 2018;Yamborisut et al, 2018). High use of pressure could be expected amongst mothers who have thin, underweight or lower BAZ child.…”
Section: Discussionmentioning
confidence: 99%
“…They restricted their child from eating too much to ensure the child did not gain weight. The use of restriction to weight may mediate the association between child obesity and restriction (Yamborisut et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation